A new, challenging benchmark for nonlinear system identification. (1st February 2017) - Tiso, Paolo; Noël, Jean-Philippe
Abstract: The progress accomplished during the past decade in nonlinear system identification in structural dynamics is considerable. The objective of the present paper is to consolidate this progress by challenging the community through a new benchmark structure exhibiting complex nonlinear dynamics. The proposed structure consists of two offset cantilevered beams connected by a highly flexible element. For increasing forcing amplitudes, the system sequentially features linear behaviour, localised nonlinearity associated with the buckling of the connecting element, and distributed nonlinearity resulting from large elastic deformations across the structure. A finite element-based code with time integration capabilities is made available athttps://sem.org/nonlinear-systems-imac-focus-group/ . This code permits the numerical simulation of the benchmark dynamics in response to arbitrary excitation signals. Abstract : Highlights: We propose a new challenging benchmark for nonlinear structural identification. The nonlinearity is either localized or distributed, depending on the applied load. Such behaviour is due to the buckling of an element connecting two offset beams. A finite element implementation of the benchmark is briefly described. A Matlab p-code of such implementation is made available to the interested reader.